Evolution of market concentration and competition in the microfinance industry of Bangladesh - Mia, Md Aslam (Emerald, 2018)
Purpose: The purpose of this paper is to measure and track the evolution of market concentration and competition in the microfinance industry in Bangladesh by employing both the structural and non-structural measurement techniques. Design/methodology/approach: By using a unique panel data set generated from the microcredit regulatory authority (MRA) annual reports, the sample includes 169 microfinance institutions (MFIs) and covers the period 2009-2014. The authors employed the Herfindahl-Hirschman index (HHI) and concentration ratio (CR) (largest 3, 8 and 20 MFIs) as structural measurement techniques and the Lerner index as a non-structural measurement technique. In addition, four different market indicators are used as representatives of deposit and credit markets to better explain the evolution of market concentration. Findings: The results of HHI indicate that the sector is moderately concentrated and currently transitioning to an unconcentrated market. However, based on CR, the industry is still dominated by a few large MFIs. The Lerner index (non-structural approach) also confirmed that the level of competition is relatively high and likely to follow an inverted U-shape during the study period. Practical implications: The findings of this study will enhance our understanding of the market structure in the Bangladesh’s microfinance industry so as to inform important policy prescriptions. The results also provide impetus to the relatively young MRA to nurture competition in the market; simultaneously, the findings prompt management of the MFIs to cope with a competitive market environment. Originality/value: This study is one of the first of its kind that includes a large data sample of microfinance market for a single country by employing both structural and non-structural measurement approaches.